Nucleotide sequence of a cDNA coding for mitochondrial fumarase from human liver. Issue 10 (October 1986) - Kinsella, B. Therese; Doonan, Shawn
Abstract : The nucleotide sequence of a 1.46 kb cDNA, selected from a human liver library by the expression of fumarase antigenic determinants, was determined using the dideoxy chain termination method. The cDNA contained an open reading frame extending from the extreme 5′-base and coding for a protein with 468 amino acids. This protein, with the exception of an N-terminal methionine, was identified as mitochondrial fumarase. The protein showed a high degree of identity of structure with the fumarase from Bacillus subtilis (56.6 %) and a fumarase from Escherichia coli (product of the fumC gene, 59.3 %), and a lower degree of identity with the aspartase of E. coli (37.2 %).